UM PECADOR QUER NOS ENSINAR? RELIGIÃO E PODER NO EPISÓDIO DO CEGO DE NASCENÇA - Rodrigues, Maria Paula (2003)
The Man Blind by Born Episode (Jn 9,1-41; 10,19-21) is a symbolic product of the competition for religious power between the Johaninne community and Pharisees of the Synagogue, having been elaborated to provoke in the readers a questioning of the legitimacy of the religious power exercised by the Pharisees, arbitrarily configured as the monopoly of the symbolic capital of Judaism. The conflict is established in so far as the Johannine community starts to compete with the Pharisees for this power, in order to attend to its own socio-religious interests. The competition is especially tangible in the confrontation between peculiar interpretations of fundamental symbols of the Jewish tradition, such as retribution, sabbat and prophecy. The confronting of the Pharisees on the part of Jewish lay members of the Johannine community invites to a symbolic revolution which proposes that lay people of the Johannine community should asume the prophetic function to dispute for the symbolic goods of Judaism.(AU)